Endotoxin-polluted medium in a human in vitro fertilization program - Snyman, E; Van der Merwe, J V (Fertility and sterility, 1986)
Optimal quality control measures to obtain the highest possible success rate for an in vitro fertilization and embryo transfer program is important in any program. Poor results obtained during a cycle where no pregnancies were achieved necessitated an investigation into possible causes. A suspected contamination of the multidistilled water utilized in medium preparation was confirmed. During a successful cycle with no endotoxins present, a pregnancy rate of 27.2% was achieved. This is higher than the 6.3% pregnancy rate achieved in another cycle where endotoxins were isolated in the media. This article illustrates cell morphologic and ultrastructural changes which could be ascribed to the presence of these endotoxins.